Unmet Need for Family Planning Among Women of Reproductive Age in Plateau State Nigeria (International Journal of Scientific Research and Management (IJSRM), 2018)
Family planning provides individuals and couples the ability to adequately space each pregnancy. Contraceptive uptake is still low in developing countries. This study aims to determine the proportion of women with unmet need for family planning in plateau State. Methods and materials: This was a cross sectional study, employing quantitative and qualitative data collection techniques. Multistage sampling technique was used to select 300 study participants across the three senatorial zones in Plateau State. A semi structured interviewer administered questionnaire was used to obtain information from study participants while a Focussed Group Discussion (FGD) guide was used to conduct FGDs among women. Data was analysed using SPSS version 23. Results: The mean age of respondents was 25.4 years. The proportion of women currently using any form of contraceptive was 36%. Fifty-six percent of the respondents had unmet need for family planning. Educational status and parity were statistically significantly associated with having unmet need for family planning. In the FDGs most women of lower parity narrated that they would like to limit and space their pregnancies but were not using family planning commodities for fear of infertility, back ache, headache and complication such as convulsion in pregnancy. Conclusion: The use of family planning commodities is low and unmet need for family planning high in Plateau State. Interventions such as health education targeting mothers may reduce the proportion of women with unmet need for family planning. This will enable women adequately space and limit their pregnancies and reduce maternal morbidity and mortality. Key words: family planning, unmet need, limiting pregnancy, spacing pregnancy.